Macroeconomic Determinants of Unemployment in Somalia: The Case of Okun’s Law and the Phillips Curve - Warsame, Abdimalik Ali; Ali, Abdullahi Osman; Hassan, Ali Yusuf; Mohamed, Mohamed Osman (Asian Economic and Financial Review, 2022)
This study aims to assess the impact of economic growth and inflation on unemployment in Somalia by testing the Phillips curve and Okun’s law hypothesis utilizing the autoregressive distributed lag (ARDL) model and time series data covering the period from 1991 to 2017. The empirical results reveal the existence of long-run cointegration among the variables. Moreover, a negative relationship is established between economic growth and unemployment both in the short run and long run, hence confirming the validity of Okun’s law hypothesis in Somalia. The impact of inflation on unemployment is inconsequential in the long run, although a strong negative association exists in the short run, thus supporting the presence of the Phillips curve hypothesis in Somalia in the short run. The study recommends that policymakers should enact policies that favor economic growth to mitigate unemployment and create a balance between the required level of inflation and unemployment in Somalia.